Effect of Chemical Castration Using High Osmolarity Solutions on Spermatological Parameters in Rats - Kaya, Seyma Ozer; Canpolat, İbrahim; Akın, Hasan (My University, 2025)
In study, the changes in spermatological parameters in rats subjected to chemical castration with high osmolarity solutions were investigated. In study, 8 male rats were used in each group. No chemicals were applied to rats in control group. Rats in second group were sterilized surgically. 0.9% physiological saline was administered to 3rd group, 0.9% physiological saline and 10% calcium chloride to 4th group, 20% mannitol to 5th group, 20% mannitol and 10% calcium chloride to 6th group, 20% dextrose to 7th group, 20% dextrose and 10% calcium chloride solutions were administered intratesticularly to 8th group at dose of 0.1 ml/100gr. Andrological findings compared to control group; it was determined that there was a significant difference in sperm motility and sperm density (p<0.001) in groups 3, 5, 7. However, it was observed that there was no difference in rate of abnormal spermatozoon. In groups 2, 4, 6, 8, motility, density, abnormal sperm count and epididymis weights could not be measured because sperm cells could not be collected. In addition, it was determined that the weights of epididymis and right cauda epididymis in groups 3, 5, 7 decreased compared to control (p<0.05), while in groups 2, 4, 6, 8, measurements could not be made because tissue samples could not be taken, and weights of testicles, vesicle seminalis and prostate decreased significantly (p<0.001) compared to control. In conclusion; it has been concluded that giving high osmolarity solutions in combination with calcium chloride will be much more effective in intratesticular chemical sterilization process.
Keywords: Rat; calcium chloride; spermatological parameters; Chemical castration